Extended spectrum β-lactamases in urinary isolates of Escherichia coli - prevalence and susceptibility pattern at a tertiary care hospital - Chauhan, Sapna; Mahawal, Bhim Singh; Ramola, Durgesh Chand (International Journal of Research in Medical Sciences, 2017)
Introduction: Urinary Tract infections caused by Escherichia coli have become a significant global public health problem. The resistance to β- lactam antibiotics in these clinically important gram negative bacteria further adds to the problem. Knowledge about their prevalence is essential to guide towards appropriate antibiotic treatment. The study was thus undertaken to know prevalence and susceptibility pattern of Extended spectrum β - lactamase (ESBL) producing Escherichia coli isolates among urinary samples. Methods: A total of 216 E. coli isolates in urinary samples were studied for ESBL production by using CLSI Phenotypic screening and confirmatory tests. Results: 53% of E.coli isolates were ESBL producers. The susceptibility of ESBL producers to Imipenem, Tigecycline and Nitrofurantion was found to be 100%, 100% and 88% respectively. A high degree of associated resistance to Amikacin, Co-trimoxazole and Quinolones was found in ESBL producers. Majority of ESBL producers were detected among patients admitted in various ICUs and surgery ward. Conclusion: Our study shows presence of ESBL producer E.coli in large number of urinary isolates.